Compact City Strategies from the Perspective of Japan’s Location Optimization Plan : Focusing on the BUG Region - Kamata, Yoko; Nam, Kwang-Woo (Journal of Korea Planning Association, 2025)
Local cities in South Korea are experiencing various urban challenges due to ongoing population decline and aging. Japan’s Location Optimization Plan (LOP), a compact city policy, has gained attention as a reference model. This study aimed to derive compact city strategies tailored to regional characteristics by analyzing LOP inducement measures and classifying local cities in the Busan-Ulsan-Gyeongnam (BUG) metropolitan area. A cluster analysis was conducted on 43 Si-Gun-Gu units using indicators representing population characteristics, urban compactness, and urban issues. Five regional types were identified: (1) declining inner city areas, (2) underserved small cities, (3) suburban growth areas, (4) vulnerable local cities, and (5) compact urban centers. Among these, Type 2—comprising seven municipalities in the Gyeongnam region—was found to be in a particularly critical condition. While access to social overhead capital (SOC) facilities is extremely poor, there is a surplus of public facilities and residents’ health is at risk because of low levels of physical activity and limited transportation options. Therefore, urgent and proactive compact city strategies are required for this type of region. Rather than relying on land-use regulations, strategies should focus on concentrating residential and SOC facilities into accessible urban centers by providing sufficient economic incentives, reorganizing and downsizing redundant public infrastructures, and repurposing vacant land and buildings. The findings of this study offer foundational insights for developing localized and typologically informed compact city strategies in regions of South Korea facing population decline. KCI Citation Count: 0